Визначення поняття «політична відповідальність»: наукові погляди та підходи до його тлумачення - Мельнік, Юлія Павлівна; Мельнік, Ю. П.; Melnik, Yuliia P. (My University, 2020)
Необхідним складником демократичного державного правління, відносин народу і влади, громадянського суспільства й держави є політична відповідальність. Є багато конкуруючих визначень політичної відповідальності, що не сприяє інституціалізації цього поняття та його механізмів у політичній практиці. В науковій літературі є багато класифікацій політичної відповідальності, й використаний нами критерій змістових відмінностей між підходами до визначення цього поняття не є єдиним. Проте, на наш погляд, наведені визначення дозволяють краще окреслити поняття політичної відповідальності, показуючи суміжні підходи до його тлумачення. Тому це сприятиме коректному й більш точному вживанню поняття та подальшій теоретичній розробці і практичному втіленню дієвих механізмів політичної відповідальності. A democratic state is distinguished by the existence of a mechanism of political responsibility, under which the imposition of sanctions for irresponsible activities is regulated in most cases not by state coercion, but by the position of the public in general and political parties in particular. Political responsibility is a necessary component of democratic government, the relationship between the people and the government, civil society and state. There are a large number of competing definitions of political responsibility, which does not contribute to the institutionalization of this concept and its mechanisms in political practice. Initially, the term “responsibility”, first introduced into scientific usage by Alfred Ben, was interpreted as “punishment”. In the scientific literature to this day, it is widely believed that political responsibility is strongly associated with legal responsibility. The main reason for this statement is the difficulty of clearly defining the grounds for political responsibility and its specific mechanisms. There are a large number of competing definitions of political responsibility, which does not contribute to the institutionalization of this concept and its mechanisms in political practice. There are a large number of classifications of political responsibility in the scientific literature, and the criterion used by us for meaningful differences between approaches to the definition of this concept is not the only one. However, in our opinion, the above definitions allow us to better define the concept of political responsibility, showing related approaches to its interpretation. Therefore, it will contribute to the correct and more accurate application of the concept and further theoretical development and practical implementation of effective mechanisms of political responsibility. Institutions of political responsibility are diverse. The main institutional means of realizing political responsibility of state to civil society are national elections and referendums. Political responsibility of civil society to state is realized through its political institutions, the main of which are political parties, public organizations and local governments. The greatest role in ensuring the stability of democracy is played by the institutions of political responsibility in the system of higher bodies of state power and their balance as elements of the system of checks and balances. Instead, the use of the concept of political responsibility in only one of these contexts without taking into account others leads to its semantic narrowing.
Мельнік Ю. П. Визначення поняття «політична відповідальність»: наукові погляди та підходи до його тлумачення / Ю. П. Мельнік // Південноукраїнський правничий часопис. 2020. № 2. С. 9-13. Режим доступу: https://doi.org/10.32850/sulj.2020.2.2
Keywords: політична відповідальність; демократія; держава; громадянське суспільство; вищі органи держави; взаємна відповідальність; державна влада; political responsibility; democracy; state; civil society; highest bodies of state authorities; cross responsibility; state power